ROLE OF NON-WOOD FOREST PRODUCTS IN POVERTY REDUCTION AMONG TRIBALS IN WESTERN GHATS OF TAMILNADU - Soundarapandian, M.; Yamuna, G. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The enormous natural resources of Indias forests including Non-Wood forest products (NWFPs), such as medicinal and aromatic plants, leaves, seeds, nuts, fruits and gums offer employment that provide up to half the income of about 25 % of the countrys rural labor force. Despite of the potential benefits that are offered by non-wood forest products, it has been widely documented that forest still offers little in terms of opportunities for expanding livelihood options and assets required to reduce livelihood vulnerability. Based on this, a study was carried out to determine the contribution of NWFPs towards poverty reduction by assessing potentials and constraints experienced by adjacent local communities towards their exploitation. The specific objective of the study is to assess the role of NWFPs contribution to tribal income and also influence on the poverty reduction. The study was conducted in Kodaikanal and Palani range in Dindigul district of Tamil Nadu state. The data were collected personally in cooperation with forest officers and other officials of the district by using pre-tested interview schedule. The findings reveals that the 65 selected households involved for collection of myrobalam (kadukkai), honey, amla, broom grass, stone flower, pepper, and coffee. These products were easily accessible and available to them and these activities are the important source of employment and income. The tribes earned at an average per day, from the collection of NWFPs of Rs700 for broom grass, Rs.650 for kadukkai, Rs.600 for amla, Rs.500 for pepper, and Rs.400 for coffee and stone flower. Regarding honey collection, the tribes earned Rs.400 per liter. Majority of the respondents (92.3 %) were facing the problems related to lack of transport facilities for NWFPs existence of bad weather (76.9 %), deforestation(69.2 %), fluctuated market price (61.5 %), lack of storage facilities for NWFPs (56.9 %), over collection of outsiders (38.4 %), low infrastructure facilities for NWFPs (18.4 %), lack of skill oriented training for NWFPs(16.9 %) and lack of timely information for marketing of NWFPs (15.3 %). It is suggested that there is a need to take necessary steps by the government to eliminate these existing problems faced by the respondent of study area. Respondents expected nearby Ration shop and Primary health centre from the district authority.